2020
DOI: 10.1177/1541204020939638
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of Adverse Childhood Experiences on Violent Recidivism Offense-Specific?

Abstract: A growing body of literature has found that exposure to child maltreatment and other forms of family dysfunction, often conceptualized as Adverse Childhood Experiences (ACEs), are associated with delinquent and criminal behavior. Recent research has indicated that the effects of ACEs on offending may differ not only by offense type but also by sex and race/ethnicity. However, no study to-date has investigated the effects of ACEs on violent-specific recidivism, nor how these effects differ by sex- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 70 publications
(90 reference statements)
1
23
0
Order By: Relevance
“…One study found gender and racial differences in the link between ACEs and recidivism; exposure to more ACEs increased the odds of arrest for a violent felony for White males and Black females (and marginally for White females), but not Black males or Hispanic males or females (Craig & Zettler, 2020).…”
Section: Results From Remaining Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found gender and racial differences in the link between ACEs and recidivism; exposure to more ACEs increased the odds of arrest for a violent felony for White males and Black females (and marginally for White females), but not Black males or Hispanic males or females (Craig & Zettler, 2020).…”
Section: Results From Remaining Studiesmentioning
confidence: 99%
“…Higher levels of ACEs were unrelated to violent misconduct among detained females (Craig & Trulson, 2019) or to rearrest during later adolescence and early adulthood (Craig et al, 2020). One study found gender and racial differences in the link between ACEs and recidivism; exposure to more ACEs increased the odds of arrest for a violent felony for White males and Black females (and marginally for White females), but not Black males or Hispanic males or females (Craig & Zettler, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Further, our analyses failed to consider alternative offending measures, such as focusing only on serious, violent offenses. It is possible that the results may differ under a variety of offending conceptualizations as recent work has found those with more ACEs were more likely to engage in violent offenses (Craig & Zettler, 2021). This represents an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated adolescents involved in the juvenile justice system are substantially more likely to have traumatic exposure (e.g., Baglivio et al, 2014a; Kim et al, 2020) as well as suffer from multiple exposures (e.g., Dierkhising et al, 2013). Further, a dramatically expanding line of research has consistently demonstrated the deleterious effects of ACEs regarding physical and mental health in public health research (e.g., Anda et al, 2010; Flaherty et al, 2013), along with antisocial behavior, juvenile justice outcomes, and recidivism (e.g., Baglivio et al, 2015; Craig & Zettler, 2021; Fox et al, 2015; Wolff et al, 2017; Zettler et al, 2018; but see Craig et al, 2020). As youth involved with the juvenile justice system enter with more trauma and because trauma has implications for continued offending, the current study sought to examine a missing component to the ACE-offending relationship in whether trauma was also related to multiple juvenile court outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has brought about an increase in empirical inquiries surrounding ACEs and their connection to both adolescent development, more generally, and involvement with antisocial behavior and the juvenile justice system, more specifically (Abram et al, 2004; Craig & Zettler, 2021; Dierkhising et al, 2013; Evans-Chase, 2014). In the seminal public health study on ACEs, Felitti and colleagues (1998) examined the link between various forms of childhood abuse, neglect, and household dysfunction and causes of death in adulthood.…”
Section: Literature Reviewmentioning
confidence: 99%